Effects of Incentive Spirometry Exercises on Pulmonary Function and Dyspnea in Patients Undergoing Acute Coronary Artery Bypass Grafting (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Background: CABG (Coronary Artery Bypass Grafting) is a procedure that is frequently performed to treat severe cases of coronary artery disease. Postoperative pulmonary complications such as reduced pulmonary function and dyspnea frequently occur following CABG due to anesthesia, sternotomy, and reduced mobility. Respiratory physiotherapy interventions, including incentive spirometry, are commonly used to improve lung expansion and prevent pulmonary complications during the postoperative period.Objective: To study the effect of incentive spirometry exercises on pulmonary function and dyspnea in patients undergoing Coronary Artery Bypass Grafting.Methods: A randomized study was carried out with 30 patients who underwent CABG surgery, aged between 50 and 60 years. Participants were randomly allocated into two groups, each consisting of 15 participants. The experimental group (GROUP A) received conventional physiotherapy exercises along with incentive spirometry exercises, while the control group (GROUP B) received conventional physiotherapy exercises alone. The intervention was administered five sessions per week for three weeks. Pulmonary function was assessed using spirometry by measuring Forced Expiratory Volume in one second (FEV₁), and dyspnea was assessed using the Borg Dyspnea Scale before and after the intervention.Results: Experimental group shows statistically significant improvement in patients with acute coronary artery bypass grafting when compared with control group.Conclusion: Incentive spirometry exercises combined with conventional physiotherapy significantly improve pulmonary function and reduce dyspnea in patients undergoing CABG during the postoperative period.